Difference between SARS‐CoV‐2, seasonal coronavirus, influenza, and respiratory syncytial virus infection in solid organ transplant recipients. Issue 1 (14th December 2022) - Mendoza, Maria A.; Motoa, Gabriel; Raja, Mohammed A.; Frattaroli, Paola; Fernandez, Anmary; Anjan, Shweta; Courel, Steve C.; Natori, Akina; O'Brien, Cristopher B.; Phancao, Anita; Sinha, Neeraj; Vianna, Rodrigo; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic has been raging since the end of 2019 and has shown worse outcomes in solid organ transplant (SOT) recipients. The clinical differences as well as outcomes between respiratory viruses have not been well defined in this population. Methods: This is a retrospective cohort study of adult SOT recipients with nasopharyngeal swab or bronchoalveolar lavage PCR positive for either SARS‐CoV‐2, seasonal coronavirus, respiratory syncytial virus (RSV) or influenza virus from January 2017 to October 2020. The follow up period was 3 months. Clinical characteristics and outcomes were evaluated. Results: A total of 377 recipients including 157 SARS‐CoV‐2, 70 seasonal coronavirus, 50 RSV and 100 influenza infections were identified. The most common transplanted organ was kidney 224/377 (59.4%). Lower respiratory tract infection (LRTI) was found in 210/377 (55.7%) and the risk factors identified with multivariable analysis were SARS‐CoV‐2 infection, steroid use, and older age. Co‐ and secondary infections were seen in 77/377 (20.4%) recipients with bacterial pathogens as dominant. Hospital admission was seen in 266/377 (67.7%) recipients without significant statistical difference among viruses, however, ICU admission, mechanical ventilation and mortality were higher with SARS‐CoV‐2 infection. In the multivariable model, the risk factors for mortality were SARS‐CoV‐2 infection and older age. Conclusions: We found higher incidence of ICU admission, mechanical ventilation, and mortality among SARS‐CoV‐2 infected recipients. Older age was found to be the risk factor for lower respiratory tract infection and mortality for SARS‐CoV‐2, coronaviruses, RSV and influenza virus groups. Abstract :